Determining the cause of intrauterine fetal death in monochorionic twins: A case report - Xie, Anxia; Cui, Yan; Luo, Gang; Chen, Xianxia; Zhang, Xuecheng; Han, Jie; Tong, Li; Ren, Yanming; Wei, Xiaoxing (Frontiers in Medicine, 2023)
Background Determining the cause of intrauterine fetal death is essential for patients to manage their next pregnancy. However, in the majority of cases of fetal death, the cause remains unexplained despite comprehensive evaluation, especially in the cases of twins. Among twin pregnancies, conditions of monochorionic twinning, commonly regarded as monozygotic, are more complicated than dichorionic ones. Case summary We systematically evaluated the cause of fetal death for a Han Chinese woman with monochorionic twinning following in vitro fertilization/embryo transfer. Discrepant karyotypes were unexpectedly discovered between the twins. One fetus had an aneuploid male karyotype (46, XY), dup (9) (p24.3-q13), and the other had a normal female karyotype (46, XX). We considered that the male died of aberration of chromosome 9 and the female died of subsequent acute exsanguination through vascular anastomosis. Conclusion This study demonstrated the importance of recognizing the presence of monochorionic dizygotic twinning and the challenges of clinical management for twins following in vitro fertilization/double embryo transfer.